Construction method for preventing cracks in super-long underground structure based on high belite cement concrete

CN122960171APending Publication Date: 2026-10-23BEIJING JIANGONG NEW BUILDING MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611044115.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0007]基于上述技术背景,本发明的主要目的在于提供一种基于高贝利特水泥混凝土的超长地下结构抗裂施工方法,以解决现有超长地下结构开裂、裂缝发生率高、渗漏、施工效率低的缺点

Benefits of technology

(1)本发明利用高贝利特水泥低热和自修复的优点,同时通过优化高贝利特水泥的颗粒级配及跳仓法的浇筑施工方法,可实现地下超长结构微裂缝的自主愈合,提升超长结构的长期完整性,有效简化施工工序,缩短整体建筑工期,提高微裂缝自愈率,并降低裂缝发生率,减少后期裂缝的修补措施成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122960171A_ABST
    Figure CN122960171A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of underground engineering construction, and particularly relates to a super-long underground structure anti-cracking construction method based on high belite cement concrete. The anti-cracking construction method comprises the following steps: dividing a side wall area of the super-long underground structure into multiple independent pouring compartments along the length direction of the super-long underground structure; segmentally pouring each independent pouring compartment by using high belite cement concrete through a skip compartment method; after pouring is completed, removing a mold, covering a heat and moisture preservation curing film on a concrete structure surface, and performing heat and moisture preservation curing. The anti-cracking construction method can reduce the structure crack occurrence rate and improve the micro crack self-healing rate. The high belite cement concrete used can realize micro crack self-repairing, and solves the problems of underground structure concrete leakage hidden danger, long maintenance period after construction cracking, and complicated process, and the construction method is widely applicable to large-size super-long underground structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of underground engineering construction technology, specifically relating to a crack-resistant construction method for ultra-long underground structures based on high-belite cement concrete. Background Technology

[0002] With the continuous improvement of urban underground space development and utilization, the construction scale of ultra-long underground concrete structures such as basements, subway stations, and integrated utility tunnels is expanding year by year. These ultra-long underground structures are characterized by large spans, high burial depths, strong constraints from surrounding soil, and complex and humid service environments, which place stringent requirements on the crack resistance, seepage prevention, and durability of concrete structures. Concrete cracking and leakage are long-standing common technical problems in underground engineering construction. Cracks not only damage the integrity of the structure, allowing moisture and harmful media to infiltrate, accelerating steel corrosion and concrete carbonation, significantly shortening the service life of the structure, but also increase the cost of later operation, maintenance, and repair, seriously restricting the high-quality construction and development of underground engineering.

[0003] Currently, the construction of ultra-long underground concrete structures in China generally adopts the post-cast strip segmented pouring process. This process uses post-cast strips to offset the shrinkage stress of the concrete, thus avoiding structural cracking. However, this traditional process has the following inherent technical drawbacks: First, the bonding performance between the new and old concrete at the post-cast strip is poor, and gaps easily form at the interface, becoming weak points for water leakage and making subsequent waterproofing and leakage control difficult. Second, the post-cast strip requires a static curing period, resulting in fragmented construction procedures and preventing continuous pouring and forming of the structure, significantly extending the overall construction period and reducing construction efficiency. Third, the processes of roughening, cleaning, and secondary pouring of the post-cast strip are cumbersome, resulting in high labor and material consumption and high overall construction costs. Furthermore, conventional cast-in-place concrete generally uses ordinary Portland cement, which has a rapid hydration heat release rate and a high total heat release. This leads to a significant internal temperature rise after concrete pouring, resulting in excessive temperature differences between the inside and outside of the structure, easily generating thermal stress and inducing early non-structural cracks.

[0004] To address concrete cracking, high-belite cement concrete with low heat of hydration is being gradually adopted in existing technologies. However, current construction methods for high-belite cement concrete still follow conventional construction schemes for ordinary concrete, lacking a dedicated and refined construction management system. This results in a disconnect between material properties and construction methods. Conventional temperature control methods rely on single monitoring points and have low levels of intelligence, failing to achieve real-time monitoring of the concrete's internal temperature and stress throughout the entire process. They also struggle to accurately control the temperature difference between the inside and outside of the structure and internal temperature peaks. Traditional curing methods have poor moisture retention and insulation effects, and curing membranes have limited functionality, making them unsuitable for different high and low temperature construction environments. This leads to uncontrolled concrete cooling rates and a tendency to develop shrinkage cracks. Furthermore, conventional construction methods do not address structural reinforcement of vulnerable areas such as side walls and roof slabs, resulting in a single level of crack resistance protection.

[0005] In addition, the existing construction method of skip-pour is subject to rough control standards. The pouring length of a single section and the interval between adjacent sections often lack precise quantitative indicators, resulting in poor adaptability. It cannot fully utilize the material advantages of high belite cement concrete, such as low heat and low shrinkage. The self-healing performance of the material is difficult to activate effectively, and the self-healing effect of micro-cracks is not good. There is still a risk of minor leakage, which is difficult to meet the construction requirements of ultra-long underground structures that are crack-free, leak-free, and durable.

[0006] In summary, there is an urgent need to develop a specific crack-resistant construction method for particle-graded self-healing high-belite cement concrete. Summary of the Invention

[0007] Based on the above technical background, the main objective of this invention is to provide a crack-resistant construction method for ultra-long underground structures based on high-belite cement concrete, so as to solve the shortcomings of existing ultra-long underground structures such as cracking, high crack incidence, leakage, and low construction efficiency.

[0008] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0009] This invention provides a crack-resistant construction method for ultra-long underground structures based on high-Belitte cement concrete, the crack-resistant construction method comprising the following steps: Step 1: Along the length of the pre-constructed ultra-long underground structure, divide the side wall area of ​​the ultra-long underground structure into multiple independent pouring chambers; Step 2: Before pouring, add a steel reinforcement mesh to the side wall area; Step 3: High-Belly cement concrete is used to pour the independent pouring sections of the side wall area at intervals using the skip pouring method. After the pouring is formed, the pouring sections are demolded, and a heat-insulating and moisture-retaining curing film is covered on the surface of the concrete structure after demolding for heat-insulating and moisture-retaining curing.

[0010] The steps described above are described in detail below.

[0011] In step 1, the main structure of the ultra-long underground structure is divided into a bottom plate area, a side wall area, a top plate area, and a side wall area that are connected in sequence in a sectional direction perpendicular to its length.

[0012] During the pouring process, the bottom slab area of ​​the ultra-long underground structure is poured first, followed by the side wall area, and finally the top slab area.

[0013] The sidewall area of ​​the ultra-long underground structure is divided into multiple independent casting chambers with a length of 15 to 28 m along the length direction.

[0014] Preferably, the sidewall area of ​​the ultra-long underground structure is divided into multiple independent pouring chambers with a length of 22 m along the length direction.

[0015] In this invention, the side wall area refers to the vertically erected concrete wall structure on both sides of the ultra-long underground structure. It is the core component for vertical load-bearing and soil retention / waterproofing of the ultra-long underground structure, connecting the bottom slab area and the top slab area, and is continuously arranged along the longitudinal length of the ultra-long underground structure. This area is subjected to long-term pressure from the outer soil and groundwater, resulting in high concrete confinement stress. Furthermore, the vertical components are difficult to maintain and retain moisture, making them highly susceptible to shrinkage cracks and temperature cracks.

[0016] This invention differs from conventional construction methods that only focus on the crack resistance of the base slab. Instead, it specifically strengthens the weak areas of the side walls that are prone to cracking and leakage by increasing the density of the steel mesh. Combined with the self-healing properties of high-belite cement concrete and a temperature-controlled curing system using a skip-pour method, this invention solves the problem of cracking and leakage in the side wall areas of ultra-long underground structures.

[0017] The term "casting chamber" refers to a space enclosed by formwork for pouring concrete during the concrete pouring process. Concrete pouring into the chamber refers to the construction process of pouring the mixed concrete into the chamber. Also called a skip-casting section or casting section, a casting chamber is a standardized, independent construction unit in the construction of ultra-long underground concrete structures. It is divided by formwork, independently shaped, and can be poured separately. It is the basic construction module of the skip-casting method.

[0018] This invention divides the sidewall area of ​​an ultra-long underground structure into independent pouring chambers of the aforementioned length and uses a skip-chamber method for segmented pouring construction, which can effectively reduce the risk of cracking caused by structural shrinkage after pouring construction.

[0019] In step 2, a steel reinforcement anti-crack mesh is added to the side wall area of ​​the ultra-long underground structure. The size of the steel reinforcement anti-crack mesh is Φ (4~8)mm×(80~120)mm×(80~120)mm.

[0020] Preferably, the dimensions of the steel reinforcement anti-crack mesh are Φ6 mm × 100 mm × 100 mm.

[0021] The present invention adds the above-mentioned fine-diameter steel reinforcement anti-crack mesh to the side wall area, which can improve the crack resistance of ultra-long underground structures. Experiments have shown that adding the above-mentioned steel reinforcement anti-crack mesh can significantly improve the crack resistance and stability of ultra-long underground structures.

[0022] The fine-diameter steel reinforcement anti-crack mesh is welded from CRB600H high-ductility cold-rolled ribbed steel bars. The overlap length of the mesh is not less than 200 mm and it is firmly tied with binding wire. During installation, it is 30-40 mm away from the inside of the template. This invention adds steel reinforcement anti-crack mesh to key local parts of stress concentration areas such as external corners (external corners refer to protruding corners, also called external corners, such as the four large corners of the exterior wall of a building. Generally, the outward-facing corners formed by the protrusion of a solid part are called external corners, and the inward-facing corners formed by the concave part are called internal corners. For example, the vertical corners around the ventilation ducts on the roof are external corners) and around openings. The size of the steel reinforcement anti-crack mesh is increased to Φ6mm×75mm×75mm. The uniformly distributed high-density steel reinforcement network can effectively disperse shrinkage stress, limit the early propagation of microcracks, and keep the width of microcracks below 0.1 mm, effectively improving the surface crack resistance safety of underground structures.

[0023] In step 3, the skip-pour method is a segmented pouring construction method for ultra-long and long-volume concrete without post-pouring strips. It involves dividing the ultra-long underground structure into several independent pouring sections and employing an intermittent, skip-pouring, batch-based pouring approach. Odd-numbered sections are poured first, and adjacent sections are poured only after the earlier poured concrete has completed early hydration shrinkage, stress release, and reached the specified curing age. This method utilizes the construction interval between adjacent sections to release the temperature and drying shrinkage stresses of the concrete, eliminating the need for traditional post-pouring strips and achieving continuous, integral molding of the poured structure, thus achieving the construction objectives of crack resistance and seepage prevention.

[0024] The post-cast strip pouring construction method refers to the practice of leaving temporary construction joints at corresponding positions in the foundation slab, walls, and beams during building construction to prevent harmful cracks that may occur in cast-in-place reinforced concrete structures due to uneven temperature and shrinkage, in accordance with design or construction specifications. This temporarily divides the structure into several parts, and after a certain period of time, the concrete of the construction joint is poured after the internal shrinkage of the components, and then the structure is connected into a whole.

[0025] Specifically, in this invention, the method of intermittently pouring the independent pouring sections of the sidewall area using the skip-pour method is as follows: The independent pouring sections of the sidewall area are divided along their length in odd-even order. A staggered, skip-pour construction method is adopted. First, all odd-numbered independent pouring sections are poured with high-Belitone cement concrete. After the concrete in the odd-numbered sections has completed early hydration shrinkage, stress release, and reached the specified curing age, the adjacent pouring sections are poured. 7-10 days after the odd-numbered sections are poured, the even-numbered sections adjacent to them are then poured. This skip-pour method allows the first poured concrete to complete temperature rise and fall and early shrinkage deformation. After eliminating adjacent constraint stresses, the post-pouring strip is eliminated. Combined with the waterproof construction of the construction joints, this achieves an overall crack-resistant construction method for ultra-long underground structures.

[0026] Preferably, nine days after the odd-numbered pouring chambers are poured, the even-numbered pouring chambers adjacent to each odd-numbered pouring chamber are then poured.

[0027] During the pouring process, the temperature of the concrete poured into the independent pouring chamber must be strictly controlled to be ≤28℃.

[0028] Preferably, during the pouring process, the temperature of the concrete poured into the independent pouring chamber is strictly controlled to be ≤25℃.

[0029] After concrete pouring, temperature and stress sensors are pre-installed before formwork closure, positioned at five points: top, middle, bottom, center, and edge. This enables intelligent temperature and stress monitoring throughout the entire process, with real-time temperature measurement around the clock. Adjusting the thickness of external curing insulation material effectively controls the internal and external temperature difference of the concrete to ≤25℃. High-belite cement concrete, characterized by low heat of hydration, can achieve an internal maximum temperature rise of ≤45℃. Actual measurements showed that the highest internal temperature peak of the concrete in this ultra-long underground structure was 33℃, with a maximum internal and external temperature difference of 12℃, far below the 25℃ control target. A smaller temperature difference results in lower temperature stress, significantly reducing the risk of concrete cracking. Insulation and curing measures can be adjusted promptly based on temperature measurements to control the internal and external temperature difference within the set range (internal maximum temperature rise ≤45℃), keeping shrinkage stress within a controllable and safe range. This significantly reduces the early shrinkage crack suppression effect of the construction process described in this invention, lowering the overall crack incidence rate by over 90%.

[0030] This invention completely eliminates the traditional post-pouring strip, implements a skip-pouring method, and uses steel plate waterstops at the joints of adjacent pouring sections to achieve joint waterproofing. This invention uses high-pressure water jet cleaning during construction joint cleaning, avoiding the waterproofing risks caused by incomplete roughening or cleaning with conventional methods or mechanical chiseling, thus eliminating weak points for joint leakage and improving the waterproofing durability of underground structures.

[0031] To control the risk of concrete segregation caused by excessive concrete pouring height, this invention optimizes the design by setting a pouring channel every 2 to 4 m, preferably every 3 m. A flexible hose is pre-installed in the pouring channel to effectively control the pouring height and ensure the quality of pouring and vibration.

[0032] The high-belite cement concrete comprises the following raw materials in parts by weight: 200-240 parts high-belite cement, 770-830 parts sand, 1000-1100 parts crushed stone, 160-200 parts fly ash, 6-7 parts admixtures, and 370-430 parts cementitious materials.

[0033] Preferably, the high-belite cement concrete comprises the following raw materials in parts by weight: 220 parts high-belite cement, 800 parts sand, 1055 parts crushed stone, 180 parts fly ash, 6.4 parts admixture, and 400 parts cementitious material.

[0034] Preferably, the high belite cement concrete comprises the following raw materials in parts by weight: 200 parts high belite cement, 770 parts sand, 1000 parts crushed stone, 160 parts fly ash, 6 parts admixture, and 370 parts cementitious material.

[0035] Preferably, the high-belite cement concrete comprises the following raw materials in parts by weight: 240 parts high-belite cement, 830 parts sand, 1100 parts crushed stone, 200 parts fly ash, 7 parts admixture, and 430 parts cementitious material.

[0036] The particle size distribution of the high belite cement is as follows: based on the total weight of the high belite cement as 100%, coarse high belite cement particles of 60-120μm account for 25-35wt% of the total weight, medium high belite cement particles of 20-60μm account for 40-50wt% of the total weight, and fine high belite cement particles of <20μm account for the remainder.

[0037] Preferably, the particle size distribution of the high belite cement is as follows: based on the total weight of the high belite cement as 100%, coarse high belite cement particles of 60-120μm account for 30wt% of the total weight, medium high belite cement particles of 20-60μm account for 45wt% of the total weight, and fine high belite cement particles of <20μm account for 25wt% of the total weight.

[0038] Preferably, the particle size distribution of the high belite cement is as follows: based on the total weight of the high belite cement as 100%, coarse high belite cement particles of 60-120μm account for 25wt% of the total weight, medium high belite cement particles of 20-60μm account for 50wt% of the total weight, and fine high belite cement particles of <20μm account for 25wt%.

[0039] Preferably, the particle size distribution of the high belite cement is as follows: based on 100% of the total weight of the high belite cement, coarse high belite cement particles of 60-120μm account for 35wt% of the total weight, medium high belite cement particles of 20-60μm account for 40wt% of the total weight, and fine high belite cement particles of <20μm account for 25wt% of the total weight.

[0040] This invention enables high-belite cement concrete to achieve self-repair of microcracks smaller than 0.2 mm by strictly limiting the particle size distribution of high-belite cement and the proportion of high-belite cement and other raw materials, and improves the self-healing rate of microcracks in high-belite cement concrete after 28 days.

[0041] The particle size of the sand is 0.05–7.0 mm.

[0042] Preferably, the particle size of the sand is 0.1 to 5.0 mm.

[0043] The crushed stone includes crushed stone with a particle size of 5-10 mm and crushed stone with a particle size of 10-20 mm.

[0044] Preferably, the crushed stone includes crushed stone with a particle size of 6 to 9 mm and crushed stone with a particle size of 12 to 18 mm.

[0045] The fly ash has a particle size of 0.1–45 μm.

[0046] Preferably, the particle size of the fly ash is 1–35 μm.

[0047] The additive is selected from one or more of magnesium oxide expanding agent, polycarboxylate superplasticizer, and air-entraining agent.

[0048] Preferably, the additive is a magnesium oxide expanding agent.

[0049] The cementing material is selected from one or two of high-belite low-heat cement and Class I F fly ash.

[0050] Preferably, the cementing material is Class I F fly ash.

[0051] The conditions for heat preservation and moisture retention curing are as follows: a heat preservation and moisture retention curing film is used to cover the surface of the concrete structure, and the surface is kept warm and moisturized at 5-30℃ for 28-40 days.

[0052] Preferably, the conditions for heat preservation and moisture retention curing are as follows: a heat preservation and moisture retention curing film is used to cover the surface of the concrete structure, and heat preservation and moisture retention curing is carried out at 10-25℃ for 35 days.

[0053] The heat-insulating and moisturizing protective film comprises interconnected thin films. This heat-insulating and moisturizing protective film can be adjusted according to seasonal changes. In low-temperature seasons, external heat insulation is achieved by adding rock wool blankets of different thicknesses. Combined with a special protective film with embedded superabsorbent polymer particles, the superabsorbent polymer can achieve internal moisture retention, continuously maintaining a stable temperature and humidity environment on the surface of the structure and preventing the cooling rate from exceeding 2℃ / d.

[0054] Preferably, granular superabsorbent polymer is uniformly adhered to the heat-insulating and moisturizing protective film, and the granular superabsorbent polymer will form a layer of superabsorbent polymer gel after pre-wetting.

[0055] More preferably, the heat-insulating and moisturizing protective film is a composite film structure formed by three interconnected layers, including an outer layer, a middle layer and an inner layer, wherein the middle layer is located between the outer layer and the inner layer.

[0056] The outer membrane is a UV-resistant PE film, the middle membrane is a fiber mesh fabric containing superabsorbent polymer (SAP), and the inner membrane is a hydrophilic nonwoven fabric. SAP (sodium polyacrylate) resin can absorb concrete bleeding water in the initial stage of heat preservation and moisture retention curing and then slowly release moisture thereafter, maintaining a relative humidity of ≥95% at the interface. When used in conjunction with an external rock wool blanket, it can reduce diurnal temperature fluctuations to less than 5℃, significantly extending the effective period of wet curing and promoting subsequent self-healing reactions.

[0057] After the concrete is poured, the formwork of each independent pouring section is removed. A heat-insulating and moisture-retaining curing film is used to cover the surface of the concrete structure for heat-insulating and moisture-retaining curing. Superabsorbent polymer particles are adhered to the inside of the heat-insulating and moisture-retaining curing film. After pre-wetting, a layer of water-absorbing superabsorbent polymer gel is formed. The film is then adhered to the surface of the concrete structure. During curing, it fully absorbs water and is moistened. With timely water replenishment, long-term moisture-retaining curing can be achieved. Depending on the temperature measurement, a composite heat-insulating curing process using non-woven fabric or rock wool blankets can be added. The heat-insulating and moisture-retaining curing cycle described in this invention is no less than 28 days.

[0058] The superabsorbent polymer is selected from one or more of sodium polyacrylate, potassium polyacrylate, polyacrylamide, polyacrylamide-acrylic acid copolymer, and carboxymethyl cellulose.

[0059] Preferably, the superabsorbent polymer is a mixed superabsorbent polymer obtained by mixing sodium polyacrylate, potassium polyacrylate and carboxymethyl cellulose.

[0060] More preferably, the superabsorbent polymer is obtained by mixing sodium polyacrylate, potassium polyacrylate and carboxymethyl cellulose in a mass ratio of (1-3):(2-4):1.

[0061] For example, the superabsorbent polymer is obtained by mixing sodium polyacrylate, potassium polyacrylate and carboxymethyl cellulose in a mass ratio of 2:3:1.

[0062] Sodium polyacrylate has a high water absorption rate (300-800 times), expands rapidly, has good stability, and strong weather resistance. Potassium polyacrylate has the advantages of good salt resistance and faster water absorption compared to sodium polyacrylate, making it suitable for underground structures and saline-alkali environments. Carboxymethyl cellulose has good water retention and excellent compatibility with concrete. The composite curing film obtained by combining sodium polyacrylate, potassium polyacrylate, and carboxymethyl cellulose in the above-mentioned mass ratio can achieve high water absorption in the early stage of concrete pouring, and can continuously absorb water from the concrete in the later stage of curing. In addition, the good water retention and good compatibility of carboxymethyl cellulose can provide real-time water replenishment for ultra-long underground concrete structures, ensuring stable hydration.

[0063] The beneficial effects of this invention are as follows: (1) This invention utilizes the advantages of high belite cement in terms of low heat and self-healing. At the same time, by optimizing the particle size distribution of high belite cement and the skip-pour method of pouring construction, it can realize the self-healing of microcracks in underground ultra-long structures, improve the long-term integrity of ultra-long structures, effectively simplify construction procedures, shorten the overall construction period, increase the self-healing rate of microcracks, reduce the occurrence rate of cracks, and reduce the cost of subsequent crack repair measures.

[0064] (2) This invention uses the skip-construction method and adds a fine-diameter steel anti-crack mesh in the side wall area and the top slab area. At the same time, the steel anti-crack mesh is densely configured in key stress and crack-prone parts. Through multiple anti-crack measures, the cracks can be reduced from harmful cracks (width > 0.3 mm) to small and dense micro cracks with a width < 0.2 mm. At the same time, relying on the high-belite cement concrete optimized particle size distribution system and the subsequent continuous hydration reaction, the self-repair of micro cracks below 0.2 mm can be achieved, effectively realizing the anti-seepage treatment of underground structure concrete, and completely solving the disadvantages of underground structure concrete leakage hazards, long repair cycle after construction cracking, and complicated procedures. This anti-crack construction method can be widely applied to large-scale and ultra-long underground structures such as basements, subway stations, and integrated pipe corridors.

[0065] (3) By setting temperature and stress sensors before concrete formwork, the present invention can adjust the heat preservation and curing measures in a timely manner according to the temperature measurement results, control the internal and external temperature difference within the set range, control the shrinkage stress within a controllable and safe range, significantly suppress early shrinkage cracks, and greatly reduce the overall crack occurrence rate. Attached Figure Description

[0066] Figure 1 The compressive strength test curves of high belite cement and ordinary Portland cement are shown. Figure 2 The flexural strength test curves of high belite cement and ordinary Portland cement are shown. Figure 3 The adiabatic temperature rise curves of high belite cement and ordinary Portland cement are shown. Figure 4 The curves showing the effect of different cement types on the autogenous shrinkage of C40 concrete are shown. Figure 5 The temperature measurement curves of concrete containing high-belite cement are shown. Figure 6 The temperature measurement curves of concrete containing ordinary Portland cement are shown. Figure 7 The strength development curves of concrete made with different types of cement are shown. Detailed Implementation

[0067] The present invention will now be described in detail, and its features and advantages will become clearer and more apparent from these descriptions.

[0068] This invention provides a crack-resistant construction method for ultra-long underground structures based on high-Belitte cement concrete, the crack-resistant construction method comprising the following steps: Step 1: The pre-constructed ultra-long underground structure is segmented along its length. The main structure of the ultra-long underground structure is divided into a bottom slab area, a side wall area, a top slab area, and a side wall area in a tangential direction perpendicular to its length. During the pouring process, the bottom slab area is poured first, followed by the side wall area, and finally the top slab area. Before pouring, the side wall area of ​​the ultra-long underground structure is divided into multiple independent pouring chambers with a length of 15–28 m along its length.

[0069] Steel plate waterstops are used at the joints in each area to achieve waterproofing. High-pressure water jets are used to clean the construction joints. A pouring channel is set up every 3 m, and a hose is pre-installed.

[0070] Step 2: Before pouring, add steel reinforcement anti-crack mesh to the sidewall area of ​​the ultra-long underground structure. The size of the steel reinforcement anti-crack mesh is Φ (4~8) mm × (80~120) mm × (80~120) mm. Add steel reinforcement anti-crack mesh to key local areas with stress concentration, such as external corners and around openings, and adjust the size of the steel reinforcement anti-crack mesh to Φ6 mm × 75 mm × 75 mm. The steel reinforcement anti-crack mesh is made of CRB600H high-ductility cold-rolled ribbed steel bars welded together. The overlap length of the mesh is not less than 200 mm and it is firmly tied with binding wire. During installation, it should be 30~40 mm away from the inside of the formwork. Step 3: Using high-belite cement concrete, the independent pouring sections in the side wall area are poured intermittently using the skip-pour method. After the pouring is completed, the pouring sections are demolded, and a heat-insulating and moisture-retaining curing film is covered on the surface of the concrete structure after demolding for heat-insulating and moisture-retaining curing.

[0071] The method of intermittently pouring the independent pouring sections in the side wall area using the skip-pour method is as follows: Each independent pouring section in the side wall area is named in numerical order along its length, including odd-numbered pouring sections and even-numbered pouring sections. The pouring construction method of intermittent skip-pour and staggered construction is adopted. First, all odd-numbered independent pouring sections are poured with high-Belit cement concrete. After the concrete poured in the odd-numbered pouring sections has completed early hydration shrinkage, stress release and reached the specified age, the adjacent even-numbered pouring sections are poured. 7 to 10 days after the odd-numbered pouring sections are poured, the adjacent even-numbered pouring sections are poured.

[0072] During the pouring process, the temperature of the concrete poured into the independent pouring chamber is strictly controlled to be ≤25℃. After the high-belite cement concrete is poured, temperature sensors and stress sensors are preset before the formwork is closed, and they are arranged at five points: upper, middle, lower, central and edge. The entire process is intelligent temperature control and stress monitoring, and real-time temperature measurement is carried out around the clock. The temperature difference between the inside and outside of the concrete is effectively controlled to be ≤25℃ by increasing or decreasing the thickness of the external curing insulation material. Taking advantage of the low heat of hydration of high-belite cement concrete, the insulation and curing measures are adjusted in a timely manner according to the temperature measurement results to control the temperature difference between the inside and outside within the set range (maximum internal temperature rise ≤45℃).

[0073] The high-belite cement concrete is prepared by mixing the following raw materials in parts by weight: 200-240 parts by weight of high-belite cement, 770-830 parts by weight of sand, 1000-1100 parts by weight of crushed stone, 160-200 parts by weight of fly ash, 6-7 parts by weight of admixtures, and 370-430 parts by weight of cementitious materials. The particle size distribution of the high-belite cement is as follows: based on 100% of the total weight of the high-belite cement, coarse particles of 60-120 μm account for 25-35 wt% of the total weight, medium particles of 20-60 μm account for 40-50 wt% of the total weight, and fine particles <20 μm account for the remainder.

[0074] The sand has a particle size of 0.1–5.0 mm. The crushed stone includes crushed stone with a particle size of 6–9 mm and crushed stone with a particle size of 12–18 mm. The fly ash has a particle size of 1–35 μm. The admixture is a magnesium oxide expanding agent. The cementing material is Class I, F type fly ash.

[0075] After pouring, the formwork is removed, and a heat-insulating and moisture-retaining curing film is used to cover the surface of the concrete structure for heat-insulating and moisture-retaining curing. The conditions for heat-insulating and moisture-retaining curing are as follows: the heat-insulating and moisture-retaining curing film is used to cover the surface of the concrete structure and is kept at 10-25℃ for 28-40 days. The heat-insulating and moisture-retaining curing film is adhered to granular superabsorbent polymer resin. After pre-wetting, the granular superabsorbent polymer resin forms a layer of superabsorbent polymer gel. The granular superabsorbent polymer resin is prepared by mixing sodium polyacrylate, potassium polyacrylate and carboxymethyl cellulose in a mass ratio of (1-3):(2-4):1.

[0076] Example The present invention is further illustrated by specific examples below. These embodiments are only for illustrating the present invention and are not intended to limit the scope of the present invention.

[0077] Example 1 A crack-resistant construction method for ultra-long underground structures based on high-belite cement concrete, with a 120m ultra-long integrated utility tunnel project as a demonstration application, includes the following steps: Step 1: Divide the pre-constructed ultra-long underground structure into sections. The main structure of the ultra-long underground structure is divided into a bottom plate area, a side wall area, a top plate area, and a side wall area in a tangential direction perpendicular to its length. Divide the side wall area of ​​the ultra-long underground structure into multiple independent pouring chambers with a length of 22 m along the length direction.

[0078] Step 2: Before pouring, reinforced steel mesh is added to the sidewall area of ​​the ultra-long underground structure. The size of the reinforced steel mesh is Φ6 mm × 100 mm × 100 mm. Reinforced steel mesh is also added to key local areas with stress concentration, such as external corners and around openings. The size of the reinforced steel mesh is adjusted to Φ6 mm × 75 mm × 75 mm. The reinforced steel mesh is made of CRB600H high-ductility cold-rolled ribbed steel bars welded together. The overlap length of the mesh is not less than 200 mm and it is firmly tied with binding wire. During installation, it is 30-40 mm away from the inside of the formwork.

[0079] Step 3: First, pour the independent pouring chambers in batches according to the area. Then, use high-belite cement concrete to pour the independent pouring chambers in the side wall area in intervals and sections using the skip pouring method. After the pouring is formed, remove the formwork of the pouring chambers and cover the surface of the concrete structure after the formwork is removed with a heat-insulating and moisture-retaining curing film for heat-insulating and moisture-retaining curing.

[0080] The method of intermittently pouring the independent pouring sections of the side wall area using the skip-pour method is as follows: the independent pouring sections of the side wall area are divided along the length direction according to odd and even order. The construction method of intermittent skip-pour and staggered construction is adopted. First, all odd-numbered independent pouring sections are poured with high-belite cement concrete. After the concrete poured in the odd-numbered pouring sections has completed early hydration shrinkage, stress release and reached the specified age, the adjacent pouring sections are poured. Nine days after the odd-numbered pouring sections are poured, the adjacent even-numbered pouring sections are poured.

[0081] During the pouring process, the temperature of the concrete poured into the independent pouring chamber is strictly controlled to be ≤25℃. After the concrete is poured, temperature and stress sensors are preset before the formwork is closed, and they are arranged at five points: upper, middle, lower, central, and edge. The entire process is intelligently controlled for temperature and stress monitoring, and real-time temperature measurement is carried out around the clock. The temperature difference between the inside and outside of the concrete is effectively controlled to be ≤25℃ by increasing or decreasing the thickness of the external curing insulation material. Taking advantage of the low heat of hydration of high-belite cement concrete, the insulation and curing measures are adjusted in a timely manner according to the temperature measurement results to control the temperature difference between the inside and outside within the set range (maximum internal temperature rise ≤45℃). The high-belite cement concrete is prepared by mixing the following raw materials in parts by weight: 220 parts by weight of high-belite cement, 800 parts by weight of sand, 1055 parts by weight of crushed stone, 180 parts by weight of fly ash, 6.4 parts by weight of admixture, and 400 parts by weight of cementitious material. The particle size distribution of the high belite cement is as follows: based on the total weight of the high belite cement as 100%, coarse high belite cement with particles of 60-120 μm accounts for 30 wt% of the total weight, medium high belite cement with particles of 20-60 μm accounts for 45 wt% of the total weight, and fine high belite cement with particles of <20 μm accounts for 25 wt%.

[0082] The sand has a particle size of 0.1–5.0 mm. The crushed stone includes crushed stone with a particle size of 6–9 mm and crushed stone with a particle size of 12–18 mm. The fly ash has a particle size of 1–35 μm. The admixture is a magnesium oxide expanding agent. The cementing material is (Grade I, Class F fly ash).

[0083] After pouring, the formwork is removed, and a heat-insulating and moisture-retaining curing film is applied to the surface of the concrete structure for heat-insulating and moisture-retaining curing. The conditions for heat-insulating and moisture-retaining curing are as follows: the heat-insulating and moisture-retaining curing film is applied to the surface of the concrete structure and cured at 10-25℃ for 35 days. The heat-insulating and moisture-retaining curing film contains granular superabsorbent polymer (SAP), which forms a layer of superabsorbent polymer gel after pre-wetting. The SAP is prepared by mixing sodium polyacrylate, potassium polyacrylate, and carboxymethyl cellulose in a mass ratio of 2:3:1.

[0084] After 60 days of acceptance, no cracks were visible to the naked eye in the super-long underground structure. Only two cracks were found in the side wall area of ​​the 20-meter-long underground structure, and the width of each crack was less than 0.08 mm, which met the first-level crack resistance requirements and demonstrated excellent waterproof and crack-resistant performance.

[0085] Example 2 A crack-resistant construction method for ultra-long underground structures based on high-Belly cement concrete, the crack-resistant construction method comprising the following steps: Step 1: Divide the pre-constructed ultra-long underground structure into sections. The main structure of the ultra-long underground structure is divided into a bottom plate area, a side wall area, a top plate area, and a side wall area in a tangential direction perpendicular to its length. Divide the side wall area of ​​the ultra-long underground structure into multiple independent pouring chambers with a length of 28 m along the length direction.

[0086] Steel plate waterstops are used at the joints in each area to achieve waterproofing. High-pressure water jets are used to clean the construction joints. A pouring channel is set up every 3 m, and a hose is pre-installed.

[0087] Step 2: Before pouring, reinforced steel mesh is added to the side walls and top slab areas of the ultra-long underground structure. The size of the reinforced steel mesh is Φ4 mm × 80 mm × 80 mm. Reinforced steel mesh is also added to key local areas with stress concentration, such as external corners and around openings. The size of the reinforced steel mesh is adjusted to Φ6 mm × 75 mm × 75 mm. The reinforced steel mesh is made of CRB600H high-ductility cold-rolled ribbed steel bars welded together. The overlap length of the mesh is not less than 200 mm and it is firmly tied with binding wire. During installation, it is 30-40 mm away from the inside of the formwork.

[0088] Step 3: Using high-belite cement concrete, the independent pouring sections of the side wall area are poured in intervals using the skip-pour method. After the pouring is completed, the pouring sections are demolded, and a heat-insulating and moisture-retaining curing film is covered on the surface of the concrete structure after demolding for heat-insulating and moisture-retaining curing.

[0089] The method of intermittently pouring the independent pouring sections in the side wall area using the skip-pour method is as follows: the independent pouring sections in the side wall area are divided along the length direction according to odd and even order. The construction method of intermittent skip-pour and staggered construction is adopted. First, all odd-numbered independent pouring sections are poured with high-belite cement concrete. After the concrete poured in the odd-numbered pouring sections has completed early hydration shrinkage, stress release and reached the specified age, the adjacent pouring sections are poured. Ten days after the odd-numbered pouring sections are poured, the adjacent even-numbered pouring sections are poured.

[0090] During the pouring process, the temperature of the concrete poured into the independent pouring chamber is strictly controlled to be ≤25℃. After the concrete is poured, temperature and stress sensors are preset before the formwork is closed, and they are arranged at five points: upper, middle, lower, central, and edge. The entire process is intelligently controlled for temperature and stress monitoring, and real-time temperature measurement is carried out around the clock. The temperature difference between the inside and outside of the concrete is effectively controlled to be ≤25℃ by increasing or decreasing the thickness of the external curing insulation material. Taking advantage of the low heat of hydration of high-belite cement concrete, the insulation and curing measures are adjusted in a timely manner according to the temperature measurement results to control the temperature difference between the inside and outside within the set range (maximum internal temperature rise ≤45℃). The high-belite cement concrete is prepared by mixing the following raw materials in parts by weight: 200 parts by weight of high-belite cement, 770 parts by weight of sand, 1000 parts by weight of crushed stone, 160 parts by weight of fly ash, 6 parts by weight of admixture, and 370 parts by weight of cementitious material. The particle size distribution of the high belite cement is as follows: based on the total weight of the high belite cement as 100%, coarse particles of 60-120μm account for 25wt% of the total weight, medium particles of 20-60μm account for 50wt% of the total weight, and fine particles of <20μm account for 25wt%.

[0091] The sand has a particle size of 0.1–5.0 mm. The crushed stone includes crushed stone with a particle size of 6–9 mm and crushed stone with a particle size of 12–18 mm. The fly ash has a particle size of 1–35 μm. The admixture is a magnesium oxide expanding agent. The cementing material is Class I, F type fly ash.

[0092] After pouring, the formwork is removed, and a heat-insulating and moisture-retaining curing film is applied to the surface of the concrete structure for heat-insulating and moisture-retaining curing. The conditions for heat-insulating and moisture-retaining curing are as follows: the heat-insulating and moisture-retaining curing film is applied to the surface of the concrete structure and cured at 10-25℃ for 28 days. The heat-insulating and moisture-retaining curing film contains granular superabsorbent polymer (SAP), which forms a layer of superabsorbent polymer gel after pre-wetting. The SAP is prepared by mixing sodium polyacrylate, potassium polyacrylate, and carboxymethyl cellulose in a mass ratio of 1:2:1.

[0093] After 60 days of acceptance, the ultra-long underground structure showed no visible cracks and excellent waterproof and crack-resistant properties.

[0094] Example 3 A crack-resistant construction method for ultra-long underground structures based on high-Belly cement concrete, the crack-resistant construction method comprising the following steps: Step 1: Divide the pre-constructed ultra-long underground structure into sections. The main structure of the ultra-long underground structure is divided into a bottom plate area, a side wall area, a top plate area, and a side wall area in a tangential direction perpendicular to its length. Divide the side wall area of ​​the ultra-long underground structure into multiple independent pouring chambers with a length of 15 m along the length direction.

[0095] Steel plate waterstops are used at the joints in each area to achieve waterproofing. High-pressure water jets are used to clean the construction joints. A pouring channel is set up every 3 m, and a hose is pre-installed.

[0096] Step 2: Add reinforcing steel mesh to the side walls and top slab areas of the ultra-long underground structure. The dimensions of the reinforcing steel mesh are Φ8 mm × 120 mm × 120 mm. Add reinforcing steel mesh to key local areas with stress concentration, such as external corners and around openings, and adjust the mesh size to Φ6 mm × 75 mm × 75 mm. The reinforcing steel mesh is made of CRB600H high-ductility cold-rolled ribbed steel bars, welded together. The overlap length of the mesh is not less than 200 mm and it is securely tied with binding wire. During installation, it should be 30–40 mm away from the inside of the formwork.

[0097] Step 3: Using high-belite cement concrete, the independent pouring sections of the side wall area are poured in intervals using the skip-pour method. After the pouring is completed, the pouring sections are demolded, and a heat-insulating and moisture-retaining curing film is covered on the surface of the concrete structure after demolding for heat-insulating and moisture-retaining curing.

[0098] The method of intermittently pouring the independent pouring sections of the side wall area using the skip-pour method is as follows: the independent pouring sections of the side wall area are divided along the length direction according to odd and even order. The construction method of intermittent skip-pour and staggered construction is adopted. First, all odd-numbered independent pouring sections are poured with high-belite cement concrete. After the concrete poured in the odd-numbered pouring sections has completed early hydration shrinkage, stress release and reached the specified age, the adjacent pouring sections are poured. Seven days after the odd-numbered pouring sections are poured, the adjacent even-numbered pouring sections are poured.

[0099] During the pouring process, the temperature of the concrete poured into the independent pouring chamber is strictly controlled to be ≤25℃. After the concrete is poured, temperature and stress sensors are preset before the formwork is closed, and they are arranged at five points: upper, middle, lower, central, and edge. The entire process is intelligently controlled for temperature and stress monitoring, and real-time temperature measurement is carried out around the clock. The temperature difference between the inside and outside of the concrete is effectively controlled to be ≤25℃ by increasing or decreasing the thickness of the external curing insulation material. Taking advantage of the low heat of hydration of high belite cement concrete, the insulation and curing measures are adjusted in a timely manner according to the temperature measurement results to control the temperature difference between the inside and outside within the set range (maximum internal temperature rise ≤45℃). The high belite cement concrete is prepared by mixing the following raw materials in parts by weight: 240 parts by weight of high belite cement, 830 parts by weight of sand, 1100 parts by weight of crushed stone, 200 parts by weight of fly ash, 7 parts by weight of admixture, and 430 parts by weight of cementitious material. The particle size distribution of the high belite cement is as follows: based on the total weight of the high belite cement as 100%, coarse particles of 60-120μm account for 35wt% of the total weight, medium particles of 20-60μm account for 40wt% of the total weight, and fine particles of <20μm account for 25wt%.

[0100] The sand has a particle size of 0.1–5.0 mm. The crushed stone includes crushed stone with a particle size of 6–9 mm and crushed stone with a particle size of 12–18 mm. The fly ash has a particle size of 1–35 μm. The admixture is a magnesium oxide expanding agent. The cementing material is Class I, F type fly ash.

[0101] After pouring, the formwork is removed, and a heat-insulating and moisture-retaining curing film is applied to the surface of the concrete structure for heat-insulating and moisture-retaining curing. The conditions for heat-insulating and moisture-retaining curing are as follows: the heat-insulating and moisture-retaining curing film is applied to the surface of the concrete structure and cured at 10-25℃ for 40 days. The heat-insulating and moisture-retaining curing film contains granular superabsorbent polymer (SAP), which forms a layer of superabsorbent polymer gel after pre-wetting. The SAP is prepared by mixing sodium polyacrylate, potassium polyacrylate, and carboxymethyl cellulose in a mass ratio of 3:4:1.

[0102] After 60 days of acceptance, the ultra-long underground structure showed no visible cracks and excellent waterproof and crack-resistant properties.

[0103] Comparative Example Comparative Example 1 The crack-resistant construction was carried out in a similar manner to Example 1, except that ordinary silicate concrete was used for crack-resistant construction in this comparative example.

[0104] The ordinary silicate concrete comprises the following raw materials in parts by weight: 260 parts ordinary silicate cement, 808 parts sand, 987 parts crushed stone, 85 parts fly ash, 85 parts slag powder, 7.74 parts admixture, and 430 parts cementitious materials.

[0105] Experimental Example Experiment Example 1 Performance Test The compressive and flexural strengths of the cement used in Example 1 and Comparative Example 1 were tested according to GB / T17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". The test results are as follows: Figure 1 , Figure 2 As shown in Tables 1 and 2.

[0106] Table 1 Compressive strength test results

[0107] Table 2 Flexural Strength Test Results

[0108] from Figure 1Table 1 shows that in the first 7 days, the compressive strength of high-belite cement was lower than that of ordinary Portland cement. However, as time progressed, continuing until the 28th day, the compressive strength of high-belite cement began to exceed that of ordinary Portland cement. Figure 2 As shown in Table 2, in the first 7 days, the flexural strength of high belite cement was lower than that of ordinary Portland cement. As time went on, up to the 28th day, the flexural strength of high belite cement began to exceed that of ordinary Portland cement, indicating that high belite cement has a higher flexural strength in the later stage.

[0109] High-Belit cement's higher late-stage flexural strength can significantly improve the bending and tensile strength of mortar and concrete matrices, effectively resisting bending stress caused by load, temperature and humidity changes, and shrinkage deformation during structural service. It also reduces the probability of microcracks and through cracks on the structural surface, which is beneficial to improving the long-term crack resistance and stability of the structure and delaying crack propagation.

[0110] Experiment Example 2: Adiabatic Test The thermal insulation performance of the cement used in Example 1 and Comparative Example 1 was tested. The thermal insulation test standard was GB / T50082-2024 "Standard for Test Methods of Long-Term Performance and Durability of Concrete". The test results are as follows: Figure 3 As shown.

[0111] Figure 3 As can be seen from the adiabatic temperature rise of the concrete, the adiabatic temperature rise of the C40-50%FA cement concrete with high belite content (45% - after calculation, the proportion of high belite cement is not actually 45%, please verify) is significantly lower than that of ordinary Portland cement OPC concrete. The adiabatic temperature rise of the concrete containing high belite cement is 8.13℃ lower than that of the concrete containing ordinary Portland cement. The above results indicate that the adiabatic temperature rise of the concrete containing high belite cement is lower.

[0112] High-Belit cement exhibits a lower adiabatic temperature rise, which effectively reduces the maximum internal temperature rise of concrete, minimizes the temperature difference between the inside and outside of the structure, significantly reduces thermal tensile stress, and inhibits the initiation of early-stage temperature cracks in concrete from the source. This makes it particularly suitable for crack control in large-volume, thick concrete components. This indicates that the lower adiabatic temperature rise of high-Belit cement can significantly optimize the hydration heat release performance of concrete, improve concrete molding quality, ensure a dense and uniform matrix structure, reduce internal defects caused by uneven temperature deformation, effectively improve the long-term crack resistance and durability of concrete structures, reduce later operation and maintenance costs, and extend the service life of the structure.

[0113] Experiment Example 3: Self-shrinkage test Autogenous shrinkage tests were conducted on the concrete made from the cement used in Example 1 and Comparative Example 1, respectively. The test standard for autogenous shrinkage was GB / T50082-2024 "Standard for Test Methods of Long-Term Performance and Durability of Concrete". The method was to use a corrugated tube method dial gauge autogenous shrinkage tester to test the autogenous shrinkage properties of the two types of concrete. The zero point of the test was set at 3 hours after molding as the standard for no further settlement and plastic deformation. The deformation after 3 hours was taken as 0. The autogenous shrinkage curve was obtained by subtracting the deformation value after 3 hours from the value after processing. The test results are as follows. Figure 4 As shown.

[0114] Figure 4 As can be seen, there is a significant difference in autogenous shrinkage properties between ordinary Portland cement (OPC) and high-belite cement (HBC 45%). The autogenous shrinkage of ordinary Portland cement and high-belite cement are 490 × 10⁻⁶ and 490 × 10⁻⁶, respectively. -6 300×10 -6 The above results demonstrate that the autogenous shrinkage properties of concrete with added high-belite cement are significantly improved, and the autogenous shrinkage properties of concrete made with high-belite cement are superior to those of concrete made with ordinary Portland cement. The excellent autogenous shrinkage properties of high-belite cement effectively reduce the amount of spontaneous shrinkage deformation throughout the concrete hardening process, fundamentally alleviating internal shrinkage stress and significantly reducing the risk of constrained shrinkage cracking. Simultaneously, the lower autogenous shrinkage deformation effectively prevents the initiation and propagation of early-stage surface microcracks in concrete, ensuring the integrity of the concrete matrix, effectively improving the overall crack resistance of concrete, and significantly enhancing the long-term stability and service durability of the structure.

[0115] Experiment Example 4: Concrete Temperature Curve Testing Temperature measurements were performed on the concrete made with the cement used in Example 1 and Comparative Example 1, respectively. The testing standard was GB / T51028-2015 "Technical Specification for Temperature Measurement and Control of Mass Concrete". The temperature measurement curves of the concrete containing high-belite cement are shown below. Figure 5 As shown, the temperature measurement curve of concrete containing ordinary Portland cement is as follows: Figure 6 As shown.

[0116] from Figure 5 and Figure 6 As can be seen from the temperature measurement curves of high-belite cement concrete structures and ordinary silicate cement concrete structures, the temperature rise difference between the two is 9℃. High-belite cement concrete has a significant effect on reducing temperature rise, and the temperature peak appears later than that of ordinary cement concrete. These results indicate that concrete containing high-belite cement has the characteristics of slow early hydration, a more gradual rate of hydration heat release, easier release of temperature stress, and continuous hydration characteristics in the later stages, enabling self-repair of microcracks and reducing the risk of concrete cracking.

[0117] Experimental Example 5: Concrete Strength Test The strength of the concrete made from the cement used in Example 1 and Comparative Example 1 was tested according to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The test results are as follows: Figure 7 As shown.

[0118] from Figure 7 It can be seen that the compressive strength of concrete containing high-belite cement increases slowly with the increase of test days, while concrete containing ordinary Portland cement shows a rapid increase in early strength and a slow increase in later strength. The aforementioned strength development trend of HBC (high-belite cement) concrete is compatible with the early temperature and autogenous shrinkage deformation of concrete, avoiding tensile cracking caused by rigid constraints and effectively reducing the probability of early cracking. At the same time, the steady increase in later strength of HBC concrete provides sufficient mechanical reserves for long-term structural service, effectively resisting secondary stresses generated by environmental temperature changes and later shrinkage, inhibiting the initiation and propagation of later microcracks, and compensating for the shortcoming of the later crack resistance degradation of ordinary Portland cement.

[0119] Combining the advantages of low adiabatic temperature rise and low autogenous shrinkage, HBC achieves long-term crack resistance by preventing cracks in the early stages and controlling cracks in the later stages, which can significantly improve the overall crack resistance and long-term durability of concrete structures.

[0120] Experimental Example 6: Concrete Performance Testing The thermal temperature rise, 7-day volumetric deformation, 28-day deformation, slump, 28-day compressive strength, and impermeability grade of the sidewall area, top slab area, and bottom slab area of ​​the ultra-long underground structure obtained according to the crack-resistant construction method of Example 1 and Comparative Example 1 were tested respectively. The test standards were GB / T50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Concrete", GB / T50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures", and GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The test results are shown in Table 3.

[0121] Table 3

[0122] As shown in Table 3, the thermal insulation temperature rise of the concrete in the base slab, side walls, and top slab of Example 1 is significantly lower than that in Comparative Example 1, with lower thermal insulation temperature rise, thermal insulation temperature rise ratio, 7-day autogenous volume deformation, and 28-day deformation. Example 1 exhibits a higher level of impermeability. These results demonstrate that using the high-belite cement concrete described in this invention and employing its crack-resistant construction method can significantly reduce the thermal insulation temperature rise and volume deformation of the base slab, side walls, and top slab of ultra-long underground structures, thereby reducing the crack incidence rate and achieving good impermeability.

[0123] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A crack-resistant construction method for ultra-long underground structures based on high-Belitte cement concrete, characterized in that, The crack-resistant construction method includes the following steps: Step 1: Divide the side wall area of ​​the pre-constructed ultra-long underground structure into multiple independent pouring chambers along the length of the structure. Step 2: Before pouring, add a steel reinforcement mesh to the side wall area; Step 3: High-Belly cement concrete is used to pour the independent pouring sections of the side wall area at intervals using the skip pouring method. After the pouring is formed, the pouring sections are demolded, and a heat-insulating and moisture-retaining curing film is covered on the surface of the concrete structure after demolding for heat-insulating and moisture-retaining curing.

2. The crack-resistant construction method according to claim 1, characterized in that, In step 1, The sidewall area of ​​the ultra-long underground structure is divided into multiple independent casting chambers with a length of 15 to 28 m along the length direction.

3. The crack-resistant construction method according to claim 1, characterized in that, In step 2, A steel reinforcement anti-crack mesh is added to the side wall area of ​​the ultra-long underground structure. The size of the steel reinforcement anti-crack mesh is Φ (4~8)mm×(80~120)mm×(80~120)mm.

4. The crack-resistant construction method according to claim 1, characterized in that, In step 3, The method of using the skip-casting method to intermittently cast the independent casting sections in the side wall area is as follows: the independent casting sections in the side wall area are divided along the length direction in odd and even order. First, all the odd-numbered independent casting sections are cast with high-Belit cement concrete. After 7 to 10 days of casting, the even-numbered casting sections adjacent to the odd-numbered casting sections are then cast.

5. The crack-resistant construction method according to claim 1, characterized in that, In step 3, The temperature of the high belite cement concrete poured into the independent pouring chamber is ≤28℃.

6. The crack-resistant construction method according to claim 1, characterized in that, In step 3, The high-belite cement concrete comprises the following raw materials in parts by weight: 200-240 parts high-belite cement, 770-830 parts sand, 1000-1100 parts crushed stone, 160-200 parts fly ash, 6-7 parts admixtures, and 370-430 parts cementitious materials.

7. The crack-resistant construction method according to claim 5, characterized in that, In step 3, The particle size distribution of the high belite cement is as follows: based on the total weight of the high belite cement as 100%, coarse particles of 60-120μm account for 25-35wt% of the total weight, medium particles of 20-60μm account for 40-50wt% of the total weight, and fine particles <20μm account for the remainder.

8. The crack-resistant construction method according to claim 5, characterized in that, In step 3, The sand has a particle size of 0.05–7.0 mm; and / or, The crushed stone includes crushed stone with a particle size of 5–10 mm and crushed stone with a particle size of 10–20 mm; and / or, The fly ash has a particle size of 0.1–45 μm; and / or, The additive is selected from one or more of magnesium oxide expanding agents, polycarboxylate superplasticizers, and air-entraining agents; and / or, The cementing material is selected from one or two of high-belite low-heat cement and Class I F fly ash.

9. The crack-resistant construction method according to claim 1, characterized in that, In step 3, The conditions for heat preservation and moisture retention curing are as follows: a heat preservation and moisture retention curing film is used to cover the surface of the concrete structure, and the surface is kept warm and moisturized at 5-30℃ for 28-40 days.

10. The crack-resistant construction method according to claim 9, characterized in that, In step 3, the characteristic is that, The heat-insulating and moisturizing protective film is adhered to granular superabsorbent polymer resin. The superabsorbent polymer is prepared from one or more of sodium polyacrylate, potassium polyacrylate, polyacrylamide, polyacrylamide-acrylic acid copolymer, and carboxymethyl cellulose.